Development of Sustainable Marine Tourism Through the Pentahelix Concept in Simeulue Regency - Agatha Debby Reiza Macella; Sri Wahyu Handayani; Sudarman Sudarman (Universitas Teuku Umar, 2023)
Indonesia's maritime economic potential is now starting to be managed in an innovative and good manner, so that it can become one of the targets of development and can provide optimal benefits for the state and people of Indonesia. This very supportive maritime natural condition can certainly be developed into other potentials, one of which is tourism. This potential certainly should not be missed. Simeulue Island has many beautiful tourist spots that need to be developed. However, the beautiful natural charm is not offset by optimal management. waste management is still bad, there is an assumption that development on the beach will only provide one-sided benefits and a lack of community enthusiasm for the development of beach tourism, and the problem of minimal human resources in managing marine tourism. The purpose of this study is to analyze the development of sustainable marine tourism through the Pentahelix concept in Simeulue Regency. The method used is a qualitative method using observation, interviews and literature studies. The results of the study show that there are 5 roles studied, namely the government, which is carried out by the Disparbud and Bappeda collaborating and coordinating with each other on issues related to tourism development planning which are in the process of being prepared and further sustainable development is needed. While academics play a role in efforts to study the development of tourism and community empowerment in the field of tourism. The media play a role in helping promotions to increase tourist attractiveness, social groups through tourism awareness groups that need to be optimized again and business people who provide tourism support facilities in Simeulue Regency such as lodging, culinary, entertainment and transportation